How is the water footprint of the species Vachellia farnesiana, Amburana cearensis, and Handroanthus impetiginosus influenced by abiotic stresses as water deficit and salinity? - dos Santos, Wilma Roberta; de Souza, Luciana Sandra Bastos; Jardim, Alexandre Maniçoba da Rosa Ferraz [UNESP]; de Morais, José Edson Florentino; dos Santos, Maria Maraíza Pereira [UNESP]; de Souza, Carlos André Alves; da Silva, Thieres George Freire (Taylor & Francis, 2024)
In semi-arid regions, is necessary to explore strategies to mitigate abiotic stresses such as water deficit and salinity. This study aimed to evaluate the stress tolerance capacity of three species subjected to different water regimes and salinity levels, based on dry matter production and water use efficiency (WUE). The species Handroanthus impetiginosus, Vachellia farnesiana, and Amburana cearensis were evaluated in combination with different water regimes (50%, 75%, and 100% of reference evapotranspiration–ET0) and salinity levels (0.18, 1.50, and 1.90 dS m−1). The results show that biomass accumulation increased at 50% and 75% ET0, while the WUE decreased at 100% ET0. The salinity level (1.90 dS m−1) caused reductions in leaf dry biomass (LDB), total dry biomass (TDB), LDB/TDB ratio, and WUE. The negative effects of high salinity on plant height were greater with the application of 75% ET0. The highest WUE was obtained at 50% ET0 for A. cearensis and H. impetiginosus, while V. farnesiana obtained the highest WUE at 75% ET0. A. cearensis exhibited the highest biomass accumulation (2.58 g) and WUE (0.21 g L−1). Overall, the species can tolerate drought and salinity conditions, being sensitive to high salinity concentrations during their initial growth.
Keywords: Dry forest; reforestation; salt stress tolerance; tolerant species